2019
DOI: 10.21873/anticanres.13344
|View full text |Cite
|
Sign up to set email alerts
|

Intraductal Adaptation of the 4T1 Mouse Model of Breast Cancer Reveals Effects of the Epithelial Microenvironment on Tumor Progression and Metastasis

Abstract: Background: Low success rates in oncology drug development are prompting re-evaluation of preclinical models, including orthotopic tumor engraftment. In breast cancer models, tumor cells are typically injected into mouse mammary fat pads (MFP). However, this approach bypasses the epithelial microenvironment, potentially altering tumor properties in ways that affect translational application. Materials and Methods: Tumors were generated by mammary intraductal (MIND) engraftment of 4T1 carcinoma cells. Growth, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 55 publications
1
13
0
1
Order By: Relevance
“…The generation of orthotopic breast cancer models via the injection of breast cancer cells inside the natural cavity of the mammary ducts (intraductal) provides for the histological and molecular features of the clinical setting, high implantation rates, and effective spontaneous metastasis [125] , [130] . Unfortunately, the intraductal strategy remains technically challenging and has yet to find common use regarding nanomedicine evaluation [135] , [136] , [137] , [138] .…”
Section: Pre-clinical Breast Cancer Animal Modelsmentioning
confidence: 99%
“…The generation of orthotopic breast cancer models via the injection of breast cancer cells inside the natural cavity of the mammary ducts (intraductal) provides for the histological and molecular features of the clinical setting, high implantation rates, and effective spontaneous metastasis [125] , [130] . Unfortunately, the intraductal strategy remains technically challenging and has yet to find common use regarding nanomedicine evaluation [135] , [136] , [137] , [138] .…”
Section: Pre-clinical Breast Cancer Animal Modelsmentioning
confidence: 99%
“…Mouse models that replicate human breast cancer play an essential role in the preclinical screening of such drugs. To this end, we and others have shown that inoculation of mammary tumor cells in the murine mammary ductal environment, also referred to as the mouse intraductal (MIND) model, provides a significant advantage over the classical fat pad model as it allows to monitor disease progression from early DCIS to invasive carcinoma (IC) (3)(4)(5)(6)(7)(8)(9)(10). Recently, we at first identified the stimulatory role of macrophage polarization in ductal breakthrough and metastatic progression in triple-negative breast cancer (TNBC) using a model based on intraductal inoculation of 4T1 mammary tumor cells in syngeneic BALB/c mice, suggesting that macrophage polarization is a potential immunotherapeutic target (4).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, tumors in bilateral organs such as breast, colon, kidney or lung, show subtle but significant differences at morphological, genetic, molecular and incidence levels (Robichaux et al 2014 ; Yang et al 2018 ). Research data from our group and others (of diverse disciplines such as embryogenesis, development, molecular oncology, or cellular biology), have proposed that the asymmetric tumor microenvironment of bilateral organs could be part of the explanation for the L/R differences in cancer (Levin et al 2016 ; Ma 2013 ; Robichaux et al 2014 ; Campoy et al 2016 ; Atiya et al 2019 ; Yi et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%